PENERAPAN MODEL PEMBELAJARAN OUTDOOR STUDY PADA MATA PELAJARAN EKONOMI KELAS X IIS 2 MAN 1 PONTIANAK - Fauzi, Vita Kusnul; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis is entitled "The Application of Outdoor Study Learning Model on Economics Subjects of Class X IIS 2 MAN 1 Pontianak." The problem in this study is "How is the Implementation of Outdoor Study Learning Model in Economics Class X MAN 1 Pontianak?". The research method used in this study is an experiment with the form of Pre Experimental research and Post-test only group design research design. The use of the experimental method in this study implements problem-based learning in the learning process in the classroom so that it can see changes in learning outcomes in IIS class X IIS 2 subjects in MAN 1 Pontianak. Techniques Data collectors are carried out through interviews, observation, and tests. Data collection tools used are interview guidelines, observation sheets (Check List), and Post-Test. The results of this study: 1.) Based on the results of the research that has been done, that the application of the outdoor study learning model on the economic subjects of class X in MAN 1 Pontianak, has been adapted to the outdoor study learning syntax implemented in learning through the Learning Implementation Plan (RPP) made by economic teachers and researchers. 2) The implementation phase is carried out in accordance with the learning implementation plan (RPP) that has been designed. 3) Evaluation of the application of the outdoor study learning model on economic subjects in class X in MAN 1 Pontianak, which can be seen from the results of the post-test, between the experimental class and the class control there are differences in the results of the post-test. the results of the pre-test after being divided between an average score of 52.37, students who completed only 6 people. while the post test results obtained an average value of 72.91, it can be concluded that there are differences before and after using the outdoor learning model.Â Keyword : Outdoor Study Learning Model, Economics Subject.